Multilayered analysis of co-development of business information systems. Issue 1 (August 2015) - Aram, Michael; Neumann, Gustaf
Abstract Business information systems (BIS) comprise technological (e.g. programs), informational (e.g. content) and social artifacts (e.g. collaboration structures). Typically, such systems are constantly and collectively developed (co-developed) further by a variety of individuals within the organization. By recognizing these varying types of actors (concerning their goals, technical expertise and language means) and their predominantly developed artifact type, one can distinguish two types of subsystems:technical subsystems wherein the development of the system behavior is conducted by software developers; andbusiness subsystems dominated by end-users developing informational artifacts. So far, co-development structures within and between these subsystems are not well understood, especially the aspect that – potentially driven by appropriate measures such as the provision of domain-specific languages – co-development might shift between these subsystems. This paper presents an approach for characterizing the co-development of real-world BIS with respect to direct participation from different kinds of contributors. This multilayered approach allows us to analyze the co-development with programming languages, domain-specific languages and end-user tools. The approach is suited to assess the direct participation of individuals from different subsystems in the development of evolving BIS. We focus on the intersection of these subsystems, present appropriate metrics and a multilayered analysis scheme. Contributions to artifacts are analyzed using social network analysis to detect structural properties of continuous co-development. The application to Learn@WU, a real-world BIS, demonstrates how end-user enabling technologies have shifted the co-development effort of the system from a small group of developers to a several orders of magnitude larger group of contributors. We observed an increase of direct participation over time on both informational and executable artifacts, while the number of technical experts was more or less constant. Our approach may act as a trigger for the application and further development of rigorous instruments for assessing co-development of BIS.